Assessing the Co-Exposure Patterns of Volatile Organic Compounds and the Risk of Hyperuricemia: An Analysis of the National Health and Nutrition Examination Survey 2003–2012 - Xue Zhao; Haiyan Ding; Jian Qin; Shuli An; Shuangshuang Li; Hongqi He; Linwei Zhou; Xinjie Gong; Xia Chu (Toxics)
Background: Co-exposure to multiple volatile organic compounds (VOCs) is common in daily life. However, few studies have evaluated the associations between the patterns of simultaneous exposure to multiple VOCs and the risk of hyperuricemia. Methods: This study included 7490 adults from the National Health and Nutrition Examination Survey conducted between 2003 and 2012. The K-means clustering method was applied to cluster eight kinds of VOCs in the blood into various co-exposure patterns, including benzene, bromodichloromethane, chloroform, dibromochloromethane, 1,4-dichlorobenzene, ethylbenzene, methyl tertiary-butyl ether (MTBE), and o-xylene. Binary logistic regression analysis was utilized to assess the association between single VOCs, the co-exposure patterns of multiple VOCs, and the hyperuricemia risk. Restricted cubic spline functions were utilized to investigate the non-linear relationships. Results: Based on eight VOCs, four characteristic co-exposure patterns were generated. Compared with the low-level exposure group, the levels of volatile organic compound (VOC) co-exposure in cluster 2, characterized by relatively high levels of MTBE and moderate levels of bromodichloromethane, chloroform, and dibromochloromethane, were associated with increased hyperuricemia risk, with an odds ratio of 1.32 (1.02, 1.71). Increasing levels of bromodichloromethane and chloroform were significantly associated with an increased risk of hyperuricemia. A strong J-shaped relationship was found between MTBE and hyperuricemia. Conclusions: This study indicated that blood bromodichloromethane and chloroform were positively associated with hyperuricemia risk. Blood MTBE had a J-shaped association with hyperuricemia. In addition, the significant association of the co-exposure patterns of multiple VOCs in the blood with hyperuricemia risk was observed. Changing VOC co-exposure patterns may play a crucial role in the occurrence of hyperuricemia.